Impact Of Financial Performance In Moderating Good Corporate Governance (GCG) With Profitability - Sri Rahayu Indah Azhari; Ira Nasriani; Safriadi Darmansyah; Zul kahfi; Idayanti Nursyamsi (International Journal of Economics, Business and Innovation Research, 2025)
This study examines the impact of Good Corporate Governance (GCG) on profitability, with the disclosure of financial performance serving as a moderating factor. The research sample comprises companies listed on the SRI-KEHATI index of the Indonesia Stock Exchange from 2021 to 2023. Data analysis was conducted using the Partial Least Square (PLS) technique. The findings reveal that while GCG has a positive influence on profitability, this effect is not statistically significant. However, when financial performance—particularly solvency—is introduced as a moderating variable, the relationship between GCG and profitability becomes both positive and significant. This suggests that stronger GCG practices, when reinforced by solid financial performance, notably enhance a company's profitability